Evidence on public health interventions in humanitarian crises. Issue 10109 (18th November 2017) - Blanchet, Karl; Ramesh, Anita; Frison, Severine; Warren, Emily; Hossain, Mazeda; Smith, James; Knight, Abigail; Post, Nathan; Lewis, Christopher; Woodward, Aniek; Dahab, Maysoon; Ruby, Alexander; et al.
Summary: Recognition of the need for evidence-based interventions to help to improve the effectiveness and efficiency of humanitarian responses has been increasing. However, little is known about the breadth and quality of evidence on health interventions in humanitarian crises. We describe the findings of a systematic review with the aim of examining the quantity and quality of evidence on public health interventions in humanitarian crises to identify key research gaps. We identified 345 studies published between 1980 and 2014 that met our inclusion criteria. The quantity of evidence varied substantially by health topic, from communicable diseases (n=131), nutrition (n=77), to non-communicable diseases (n=8), and water, sanitation, and hygiene (n=6). We observed common study design and weaknesses in the methods, which substantially reduced the ability to determine causation and attribution of the interventions. Considering the major increase in health-related humanitarian activities in the past three decades and calls for a stronger evidence base, this paper highlights the limited quantity and quality of health intervention research in humanitarian contexts and supports calls to scale up this research.